Teaching similarities and differences between non directive teaching and enhancing self esteem of special education students - Senin, M.S.; Nordin, Mohd Norazmi; Abd Mutalib, Norathirah Nabila; Abd Rashid, Intan Maizura; Mustafa, Mohamad Zaid; Abdul Razzaq, Abdul Rasid; Ibrahim, Badarudin (2021)
The world of education is rich in teaching strategies that involve a variety of methods and resources. Each teaching strategy has its own characteristics and is determined based on the situation and circumstances of students. This diversity of teaching strategies makes the implementation of teaching by teachers is not static and always dynamic according to current needs. Teachers who are creative and sensitive to current changes will be able to adapt the right teaching strategies to students. Teaching strategies are not fixed, they can be modified as needed. This statement is in line with the existing needs in special education. With different levels of ability of students with special needs, then teaching strategies should also be different and creative. Of course, the appropriate strategy must be chosen to ensure that students receive the knowledge that is presented well. This review article discusses two selected teaching strategies, namely non directive teaching (NDT) and enhancing self esteem (ESE) which are seen to be suitable for special education. The discussion in this article is hoped to provide a brief overview to subsequent researchers in conducting further studies.